Ultrahigh Surface Area N‐Doped Hierarchically Porous Carbon for Enhanced CO2 Capture and Electrochemical Energy Storage. Issue 15 (27th June 2019) - Wang, Shuai; Qin, Jieqiong; Zhao, Yujuan; Duan, Linlin; Wang, Jinxiu; Gao, Wenjun; Wang, Ruicong; Wang, Changyao; Pal, Manas; Wu, Zhong‐Shuai; Li, Wei; Zhao, Dongyuan
Abstract: Facile synthesis of ultrahigh surface area porous carbons with well‐defined functionalities such as N‐doping remains a formidable challenge as extensive pore creation results in significant damage to the active sites. Herein, an ultrahigh surface area, N‐doped hierarchically porous carbon was prepared through a multicomponent co‐assembly approach. The resultant N‐doped hierarchically porous carbon (N‐HPC) possessed an ultrahigh surface area (≈1960 m 2  g −1 ), a uniform interpenetrating micropore (≈1.3 nm) and large mesopore (≈7.6 nm) size, and high N‐doping in the carbon frameworks (≈5 wt %). The N‐HPC exhibited a high specific capacitance (358 F g −1 at 0.5 A g −1 ) as a supercapacitor electrode in aqueous alkaline electrolyte with a stable cycling performance after10 000 charge/discharge cycles. Moreover, as a CO2 absorbent, N‐HPC displayed an adsorption capacity of 29.0 mmol g −1 at 0 °C under a high pressure of 30 bar. Abstract : Doping done right : N‐doped hierarchically porous carbon materials with an ultrahigh specific surface area and high N content are fabricated through a multicomponent co‐assembly method. The SiO2 component provides reinforcement to support a highly ordered mesostructured, acts as a cross‐linked network that can keep confinement of nitridation from pyrolysis, and as a poreforming agent it creates interpenetrating micropores.